Adventures of Huckleberry Finn, Chapters 01 to 05 - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Adventures of Huckleberry Finn, Chapters 01 to 05" by Mark Twain is a novel first published in 1884-1885. This sequel to "The Adventures of Tom Sawyer" follows young Huck Finn as he escapes his abusive father and embarks on a daring journey down the Mississippi River. Accompanied by Jim, a runaway slave seeking freedom, Huck confronts difficult moral choices in a society steeped in racism. Written entirely in vernacular English, this groundbreaking work combines adventure, satire, and a deeply felt portrayal of boyhood in antebellum Missouri. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Adventures_of_Huckleberry_Finn
Release date is 2004-06-27
Produced by David Widger
Keywords: Humorous stories; Bildungsromans; Boys -- Fiction; Male friendship -- Fiction; Adventure stories; Missouri -- Fiction; Race relations -- Fiction; Runaway children -- Fiction; Finn, Huckleberry (Fictitious character) -- Fiction; Fugitive slaves -- Fiction; Mississippi River -- Fiction